Improved spectral response of sensitized photoelectrodes with the optical modulation layer - Lee, Sangwook; Kim, Dong Hoe; Kim, Jin Young; Jung, Hyun Suk; Shin, Hyunho; Hong, Kug Sun (ELSEVIER SCIENCE INC, 2012)
We demonstrated that TiO2 compact layers (c-TiO2) can modulate optical transmittance of transparent conducting oxide (TCO) substrates and improve spectral response of a dye-sensitized solar cell (DSSC). The transmittance spectra of TCO substrates were controlled with the thickness of c-TiO2 layers, which in turn, influenced the incident photon-to-current conversion efficiency of DSSCs. The overall energy conversion efficiency of the DSSC with a 210 nm-thick c-TiO2 layer was increased by 16% compared to the DSSC with a 40 nm-thick c-TiO2 layer, due to the higher optical transmittance of the TCO substrate. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: SOLAR-CELL APPLICATIONS; CONVERSION; TIO2; FILM; DYES